Driving Teacher Performance: The Influence Of Principals' Transformational Leadership and Teachers' Work Discipline Through Work Motivation In Pulau Laut Utara District - Norliani; Ahmad Suriansyah; Sulistiyana; Aslamiah (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
Teacher performance is one of the primary determinants of educational quality and school effectiveness. However, teacher performance is influenced by various organizational and individual factors. This study aims to analyze the effects of principals' transformational leadership and work discipline on teacher performance through work motivation as an intervening variable in public junior high schools in Pulau Laut Utara District. This research employed a quantitative approach using a survey method. The population consisted of 137 teachers from all public junior high schools in Pulau Laut Utara District, and all participants were included using a saturated sampling technique. Data were collected through Likert-scale questionnaires and analyzed using path analysis, supported by classical assumption tests and the Sobel mediation test with IBM SPSS Statistics. The findings indicate that transformational leadership, work discipline, work motivation, and teacher performance were generally classified as high. Transformational leadership had a positive and significant effect on teacher performance (R² = 0.145) and work motivation (R² = 0.105). Work discipline exerted a positive and significant effect on teacher performance (R² = 0.863) and work motivation (R² = 0.807). Furthermore, work motivation positively and significantly influenced teacher performance (R² = 0.758). Path analysis and the Sobel test confirmed that work motivation significantly mediated the relationship between transformational leadership and teacher performance (Z = 3.88 > 1.96), as well as the relationship between work discipline and teacher performance (Z = 2.60 > 1.96). These findings demonstrate that, although transformational leadership and work discipline directly improve teacher performance, their influence is strengthened through enhanced teacher work motivation. In conclusion, principals’ transformational leadership, work discipline, and work motivation are significant determinants of teacher performance in public junior high schools in North Pulau Laut District. Work motivation functions as a significant mediating variable, highlighting the importance of fostering teachers’ intrinsic motivation alongside strengthening transformational leadership practices and cultivating a strong culture of work discipline to improve educational quality.